48.0k views
0 votes
Please help ASAP!!!! ​

Please help ASAP!!!! ​-example-1

2 Answers

2 votes

The answer is B i had this problem.

User Pablo Bianchi
by
5.2k points
3 votes

Answer: OPTION B

Explanation:

Multiply both denominators to find the Least Common Denominator:


LCD=(3y-4)(y^2)

Now, divide each original denominator by the LCD and multiply the result by each numerator. Then:


=((6y^2+2y)(y^2)-(9y-7)(3y-4))/((3y-4)(y^2))

Applying Distributive property, you get:


=(6y^4+2y^3-(27y^2-36y-21y+28))/(3y^3-4y^2)\\\\=(6y^4+2y^3-27y^2+36y+21y-28)/(3y^3-4y^2)

Add the like terms in the numerator:


=(6y^4+2y^3-27y^2+57y-28)/(3y^3-4y^2)

User Steve Danner
by
5.5k points